2001
DOI: 10.1007/pl00013001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Harpin from Four Pathovars of Pseudomonas syringae on Pea Defense Responses

Abstract: To investigate the role of the proteinaceous elicitor, harpin, on host and nonhost plants, we isolated the harpin-coding gene, hrpZ, from Pseudomonas syringae pvs. pisi, glycinea, tabaci and tomato. Effects of the recombinant harpin proteins on pea plants were analyzed and compared with the effects of the corresponding bacterial treatment. After inoculation of pea with pea pathogen P. syringae pv, p h i , the bacterial population increased and the accumulation of PAL-mRNA and pisatin was inhibited. The nonpath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Defense responses in plants elicited by macromolecules of proteic nature are usually related to systemic acquired resistance (SAR) (Wei et al, 1992a(Wei et al, , 1995Tanaka et al, 2001). However, Romeiro et al (2005Romeiro et al ( , 2010 showed that there is induced systemic resistance (ISR) in tomato by a protein synthesized by the rhizobacterium Bacillus cereus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Defense responses in plants elicited by macromolecules of proteic nature are usually related to systemic acquired resistance (SAR) (Wei et al, 1992a(Wei et al, , 1995Tanaka et al, 2001). However, Romeiro et al (2005Romeiro et al ( , 2010 showed that there is induced systemic resistance (ISR) in tomato by a protein synthesized by the rhizobacterium Bacillus cereus.…”
Section: Introductionmentioning
confidence: 99%
“…These studies may encourage research lines that eventually lead to bioproduct development. This was the case with the harpin protein synthesized by bacteria of the genera Erwinia, Ralstonia and Pseudomonas (Wei et al, 1992a(Wei et al, , 1992b(Wei et al, , 1993(Wei et al, , 1995(Wei et al, , 2000Tanaka et al, 2001;Dayan et al, 2009) that generated the commercial products Messenger ® and ProAct ® with broad-spectrum activity against phytopathogens of various crops (Dayan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, harpin Pss , harpin Pgl and harpin Pto (harpins from Pss , Pgl and Pto , respectively) elicit HR in tomato but not in soybean (Preston et al ., 1995). We also observed that the recombinant harpin Pto , harpin Pgl and harpin Ppi (harpin from Ppi ) did not elicit pea defence responses at a concentration of 6.8 µ m (Tanaka et al ., 2001). Thus, the effects of harpin vary among plant species, and leguminous plants seem to be insensitive or slightly sensitive to harpins from P. syringae .…”
mentioning
confidence: 93%